GDF: A Gamification Design Framework Powered by Model-Driven Engineering - Bucchiarone, Antonio; Cicchetti, Antonio; Marconi, Annapaola (2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2019)
Gamification refers to the exploitation of gaming mechanisms for serious purposes, like promoting behavioural changes, soliciting participation and engagement in activities, and so forth. In this demo paper we present the Gamification Design Framework (GDF), a tool for designing gamified applications through model-driven engineering mechanisms. In particular, the framework is based on a set of well-defined modelling layers that start from the definition of the main gamification elements, followed by the specification on how those elements are composed to design games, and then progressively refined to reach concrete game implementation and execution. The layers are interconnected through specialization/generalization relationships such that to realize a multi-level modelling approach. The approach is implemented by means of JetBrains MPS, a language workbench based on projectional editing, and has been validated through two gameful systems in the Education and Mobility domains. A prototype implementation of GDF and related artefacts are available at the demo GitHub repository: https://github.com/antbucc/GDF.git, while an illustrative demo of the framework features and their exploitation for the case studies are shown in the following video: https://youtu.be/wxCe6CTeHXk.